2017
DOI: 10.3389/fneur.2017.00436
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Maximum Pitch Elevation Predicts Silent Aspiration of Small Liquid Volumes in Stroke Patients

Abstract: Background and purposePreliminary evidence has shown that reduced ability to maximally raise vocal pitch correlates with the occurrence of aspiration (i.e., airway invasion by food or liquid). However, it is unclear if this simple task can be used as a reliable predictor of aspiration in stroke patients. Our aim was to examine whether maximum vocal pitch elevation predicted airway invasion and dysphagia in stroke.MethodsForty-five consecutive stroke patients (<1 month poststroke) at a rehabilitation setting pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
3
6
2
Order By: Relevance
“…Additionally, it was discovered that lower maximum F 0 was associated with higher penetration-aspiration scores. These results support the findings of the two previous studies which reported that reduced pitch glide can accurately predict aspiration on small liquid boluses [37, 38]. However, the sample size of our study was small, and results should be validated in a future study including a bigger sample size.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Additionally, it was discovered that lower maximum F 0 was associated with higher penetration-aspiration scores. These results support the findings of the two previous studies which reported that reduced pitch glide can accurately predict aspiration on small liquid boluses [37, 38]. However, the sample size of our study was small, and results should be validated in a future study including a bigger sample size.…”
Section: Discussionsupporting
confidence: 92%
“…Although previous evidence suggests that auditory-perceptual results of the pitch glide were accurate in predicting aspiration and there were adequate correlations between auditory-perceptual ratings and aspiration, in our study it was revealed that auditory-perceptual analysis of the pitch glide had inadequate sensitivity and specificity [37, 38]. Correlations between auditory-perceptual results of the pitch glide and aspiration status were also weak in the current study.…”
Section: Discussioncontrasting
confidence: 91%
See 3 more Smart Citations